Danish translation and validation of the Occupational Balance Questionnaire. (4th July 2022) - Hansen, Alice Ørts; Boll, Mette; Skaarup, Line; Hansen, Tina; Dür, Mona; Stamm, Tanja; Kristensen, Hanne Kaae
Abstract: Background: Occupational balance is a key concept in occupational science and occupational therapy. However, it is not well operationalized and instruments to evaluate occupational balance are scarce. Aim: To translate and validate a Danish version of the 10-item Occupational Balance Questionnaire (OB-Quest). Material and methods: Translation was conducted using the dual-panel approach. Thereafter, data from 262 healthy Danish students were analyzed regarding fit to the Rasch model. Results: The translation of the questionnaire to Danish required only minor cultural adaptations. Ninety percent of the participants were female. The mean age (±SD) was 26.10 (7.05) years. The reliability (person separation index) was questionable (0.63), and the scale showed multidimensionality. Two items (1 and 9) showed misfit to the Rasch model. Differential item function by gender was detected in one item (item 4). After deleting items 1 and 9 and splitting item 4 into two gender-specific items, the new 9-item scale showed good overall and individual item fit. However, reliability remained low (0.59) and some elements of the latent variable (occupational balance) were not sufficiently represented. Conclusions and significance: Further development and testing of the Danish OB-Quest is needed before implementation in clinical practice or research involving healthy subjects.